Self-perceived preparedness of undergraduate dental students in dental public universities in Malaysia: A national study - Mat Yudin, Zainab; Ali, Kamran; Wan Ahmad, Wan Muhamad Amir; Ahmad, Anisa; Khamis, Mohd. Fadhli; Brian Graville Monteiro, Nur ‘Aliya; Che Ab. Aziz, Zeti Adura; Saub, Roslan; Rosli, Tanti Irawati; Alias, Aspalilah; Abdul Hamid, Nor Faharina; Harun, Nor Asilah (John Wiley & Sons, 2019)
Aims: To evaluate the self-perceived preparedness of final-year dental undergraduate students in dental public universities in Malaysia. Methods: Final-year dental undergraduate students from six dental public universities in Malaysia were invited to participate in an online study using a validated Dental Undergraduates Preparedness Assessment Scale DU-PAS. Results: In total, about 245 students responded to the online questionnaire yielding a response rate of 83.05%. The age range of the respondents was 23-29 years with a mean age of 24.36 (SD 0.797). The total score obtained by the respondents was ranged from 48 to 100 with a mean score of 79.56 (SD 13.495). Weaknesses were reported in several clinical skills, cognitive and behavioural attributes. Conclusions: The preparedness of undergraduate students at six dental institutions in Malaysia was comparable to students from developed countries. The dental undergraduate preparedness assessment scale is a useful tool, and dental institutions may be used for self-assessment as well as to obtain feedback from the supervisors.